Genre across the curriculum - Herrington, Anne, editor; Moran, Charles, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2005)
Genre across the Curriculum will function as a ''good'' textbook, one not for the student, but for the teacher, and one with an eye on the context of writing. Here you will find models of practice, descriptions written by teachers who have integrated the teaching of genre into their pedagogy in ways that both support and empower the student writer.
The idea of genre in theory and practice: an overview of the work in genre in the fields of composition and rhetoric and new genre studies / Anne Herrington, Charles Moran -- PART ONE: GENRE ACROSS THE CURRICULUM: GENERAL EDUCATION AND COURSES FOR MAJORS -- Reading and writing, teaching and learning spiritual autobiography / Elizabeth A. Petroff -- Writing history: informed or not by genre theory? / Anne Beaufort, John A. Williams -- Mapping classroom genres in a science in society course / Mary Soliday -- "What's cool here?" Collaboratively learning genre in biology / Anne Ellen Geller -- PART TWO: GENRES IN FIRST-YEAR WRITING COURSES -- "I was just never exposed to this argument thing": using a genre approach to teach academic writing to ESL students in the humanities / Rochelle Kapp, Bongi Bangeni -- "Getting on the right side of it": problematizing and rethinking the research paper genre in the college composition course / Carmen Kynard -- The resumé as genre: a rhetorical foundation for first-year composition / Shane Peagler, Kathleen Blake Yancey -- PART THREE: MIXING MEDIA, EVOLVING GENRES -- Teaching and learning a multimodal genre in a psychology course / Chris M. Anson .. [et al.] -- The teaching and learning of web genres in first-year composition / Mike Edwards, Heidi McKee -- Writing in emerging genres: student web sites in writing and writing-intensive classes / Mike Palmquist -- What we have learned: implications for classroom practice / Anne Herrington, Charles Moran.
Keywords: English language -- Rhetoric -- Study and teaching; Interdisciplinary approach in education; Academic writing -- Study and teaching